ROOTS SEBAGAI PROGRAM PENCEGAHAN PERUNDUNGAN DI MTS ASSALAM BANTUR - Hasna Bararah Mufidah; Desy Santi Rozakiyah (Jurnal Analisa Sosiologi, 2024)
Bullying in the school environment is a serious problem that requires effective prevention measures. The role of schools is important by designing effective bullying prevention programs to suppress acts of violence in schools. MTs (Madrasah Tsanawiyah) Assalam Bantur as one of the schools implementing the roots program designed by the Indonesian government. This research is a qualitative research using case study research with the aim of being able to understand in depth about how this bullying prevention program works, its impact, and the experiences of the individuals involved in it. The results of the research show that there are four aspects that need to be fulfilled in the structural functional belonging to Persons in the implementation of the roots program at MTs Assalam Bantur, namely (1) Adaptation, the school adapts to the environment and society and the needs of students in implementing the roots program, (2) Goal Attainment, the roots program at Assalam Bantur MTs has the goal of preventing bullying at school (3) Integration, schools do not only collaborate with guidance counselors and peer counselors, but it is necessary to involve all students, teachers and stakeholders in program implementation and (4) Latency, MTs Assalam Bantur conduct continuous training to students as well as evaluate for program improvement.